Degradation of groundwater quality due to the occurrence of salty-tasted water in Bayat District, Klaten, Central Java, Indonesia - Doni Prakasa Eka Putra; Deviana Halim; Sandi Suko Widagdo; Rilo Restu Surya Atmaja (Brawijaya University, 2020)
Bayat is located in the south of central Java, Indonesia. In the quaternary deposit area, groundwater on some dug wells taste salty and previous studies discovered salty-tasted water with electrical conductivity (EC) >5000 μS/cm and chloride concentration >1000 mg/l. Local information reported that the number of wells containing salty-tasted water increased after the 6.2 Mw earthquake on May 27th, 2006 in Yogyakarta. This research aims to determine the distribution of salty-tasted groundwater and its relation with the geological condition by conducting a hydrogeological investigation. On the hydrogeological investigation, dug wells were observed for physical-chemical characteristics such as total dissolved solid (TDS) and EC; additionally, groundwater samples were collected for chloride ion analysis. Geology of the study area is mapped based on previous studies. The result showed that the high TDS/EC groundwater correlated with salty-tasted water which found in three different areas, including in the west, middle and east part of the study area. The occurrence of salty-tasted water strongly aligns with faults zone. In conclusion, deep salty-tasted water emerges not only locally near the fault zone but also associated with trapped groundwater and buried anticline. In regard to those sources, it can be predicted that in the near future more dug wells water may turn into salty-tasted water, especially in the area closed to the fault zone.